The association of neutrophil-lymphocyte ratio and prognostic nutritional index with the development to chronic critical illness and their prognosis - Chen, Xinghua; Li, Ziwei; Wei, Xing; Yao, Li (Frontiers in Nutrition, 2025)
BackgroundThe association between neutrophil-lymphocyte ratio (NLR) prognostic nutritional index (PNI) and chronic critical illness (CCI) is unclear. We aimed to explore the association between NLR and PNI with CCI and whether it could be used as a tool for risk stratification in such patients.MethodsA retrospective cohort study was conducted using the Medical Information Mart for Intensive Care-IV (MIMIC-IV) database. The data collection spanned from 2008 to 2019, and the database was sourced from Beth Israel Deaconess Medical Center in Boston. The clinical data of patients who were admitted to ICU for the first time for more than 24 h were collected, including the values of NLR and PNI on the first day of admission. The primary outcomes of the study were whether critically ill patients progressed to CCI and the in-hospital all-cause mortality rate of patients with CCI. Multivariate logistic regression models were used to analyze the relationship between NLR and PNI and outcomes, and three models were used to adjust for possible confounders. Receiver operating characteristic (ROC) curves and the area under the curve (AUC) were utilized to evaluate the predictive value of these research indicators for the outcomes. Subgroup analyses were also performed to explore whether the association of the study metrics with outcome was robust across different patient populations.ResultsA total of 5,637 critically ill patients were ultimately enrolled in the study, and 675 (12%) progressed to CCI, with in-hospital death occurring in 115 (17%) of these patients. In the adjusted model of critically ill patients progressing to CCI, the ORs for NLR and PNI were 1.050 (1.041–1.060) and 0.958 (0.944–0.971), respectively. The AUC were 0.755 (0.735–0.775) and 0.718 (0.697–0.739). In the adjusted model for in-hospital deaths in CCI patients, the ORs for NLR and PNI were 1.014 (1.003–1.025) and 0.951 (0.923–0.979), respectively. The AUC were 0.670 (0.619–0.721) and 0.677 (0.626–0.729), respectively. Results remain robust across patient populations.ConclusionHigh NLR and low PNI levels are associated with progression to CCI and in-hospital death in critically ill patients and can be used as a valid predictive tool for poor prognosis in critically ill patients.